Injuries in competitive boxing. A prospective study - Siewe, J.; Rudat, J.; Zarghooni, K.; Sobottke, R.; Eysel, P.; Herren, C.; Knöll, P.; Illgner, U.; Michael, J. (International Journal of Sports Medicine, 2015)
Boxing remains a subject of controversy and is often classified as dangerous. But the discussion is based mostly on retrospective studies. This survey was conducted as a prospective study. From October 2012 to September 2013, 44 competitive boxers were asked to report their injuries once a month. The questionnaire collected general information (training, competition) and recorded the number of bouts fought, injuries and resulting lost days. A total of 192 injuries were recorded, 133 of which resulted in interruption of training or competition. Each boxer sustained 3 injuries per year on average. The injury rate was 12.8 injuries per 1000 h of training. Boxers fighting more than 3 bouts per year sustain more injuries (p=0.0075). The injury rate does is not a function of age (age=19 vs. > 9a, p=0.53). Injuries to the head and the upper limbs occur most frequently. The most common injuries are soft tissue lacerations and contusions. Head injuries with neurological symptoms rarely occur (4.2%). Boxing has a high injury rate that is comparable with other contact sports, but most injuries are minor. Injury frequency is not a function of whether the boxer competes in the junior or adult category. Athletes fighting many bouts per year have a greater risk of injury.